Relationship of the Duration of Ventilator Support to Successful Weaning and Other Clinical Outcomes in 437 Prolonged Mechanical Ventilation Patients. (May 2017) - Sansone, Giorgio R.; Frengley, J. Dermot; Vecchione, John J.; Manogaram, Merlin G.; Kaner, Robert J.
Objective: To investigate the relationships between durations of ventilator support and weaning outcomes of prolonged mechanical ventilation (PMV) patients. Methods: Cohort study of 957 PMV patients sequentially admitted to a long-term acute care hospital (LTACH). The study population was 437 PMV patients who underwent weaning, having achieved ≥4 hours of sustained spontaneous breathing. They were divided into tertiles of mechanical ventilation (MV) durations and compared for differences (tertile A: 21-58 days, n = 146; tertile B: 59-103 days, n = 147; and tertile C: ≥104 days, n = 144). Results: Tertiles showed comparable weaning success rates and survival. As MV durations increased, LTACH postweaning days became progressively greater, whereas decannulations and discharge physical function diminished, and home discharges decreased while nursing facility discharges increased (all P < .001). Patients with lower physical function before critical illness or greater burdens of comorbidities were least likely to be weaned (all P < .001). Younger ages, lower comorbidity burdens, neurological diagnoses, higher admission prealbumin levels, and successful weaning, each independently reduced the risk of death (all P < .01). Conclusion: Durations of MV did not affect weaning success or survival, although deleterious effects were found in discharges, decannulations, LTACH postweaning days, and discharge physical function. Durations of MV alone should not guide transfer decisions for subsequent continuing care.